Pregnancy after frozen embryo transfer in mycobacterium tuberculous salpingitis: A case report and literature review - Firouzeh Ghaffari; Shokouholsadat Miralaie; Zahra Chekini; Maziar Faridi (Shahid Sadoughi University of Medical Sciences, 2020)
Background: Genital tuberculosis is a common cause of infertility due to blocked and permanently damaged fallopian tubes.Case: In this case report, we describe one extremely rare case of tuberculous salpingitis in a woman who presented with infertility. She received anti-tuberculosis (TB) treatment 10 yr prior. In vitro fertilization (IVF) and intracytoplasmic sperm injection were carried out in our institute. Then, she underwent a laparoscopic salpingectomy due to bilateral hydrosalpinx and a frozen embryo was transferred, which led to pregnancy and a healthy child.Conclusion: It was concluded that IVF and frozen embryo transfer provides treatment for tubal TB with a receptive endometrium. Laparoscopic salpingectomy prior to embryo transfer plays a critical role in predicting the occurrence of a pregnancy in a patient with hydrosalpingitis attributed to TB.